Electrolyte and battery

By using additive A containing pyridine ring and specific substituents in the electrolyte, the performance problems caused by HF generation in lithium/sodium batteries are solved, and the battery has good circulation and storage performance at room temperature and high temperatures are achieved.

CN119695277AActive Publication Date: 2025-03-25CHONGQING FUDI BATTERY RES INST CO LTD
View PDF 5 Cites 0 Cited by

Patent Information

Application Number
CN202311239189.5
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2023-09-22
Publication Date
2025-03-25
Estimated Expiration
2043-09-22

AI Technical Summary

Technical Problem

The presence of moisture in the lithium/sodium battery in the electrolyte causes HF generation, which in turn reduces the battery's circulation performance and high-temperature storage performance. It is difficult for the prior art to take into account both good circulation performance and high-temperature storage performance.

Method used

An electrolyte containing a specific additive A is adopted. The structure of additive A contains pyridine ring and amino, nitrile, and isocyanate substituents, which can effectively reduce the HF content, inhibit the dissolution of transition metal ions on the positive electrode side, and improve the stability of the interface film on the positive electrode side.

Benefits of technology

This electrolyte can significantly improve the battery's room temperature cycle performance and high-temperature storage performance, while reducing the room temperature impedance, ensuring the stability and performance of the battery under different conditions.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119695277A_ABST
    Figure CN119695277A_ABST
Patent Text Reader

Abstract

The invention provides an electrolyte and a battery. The electrolyte comprises an electrolyte salt, a solvent and at least one additive A as shown in a formula (I): # imgabs0 #, at least one pair of R1 and R4 and at least one pair of R2 and R3 contains amino groups, and the other pair of R1 and R4 and R2 and R3 contains at least one of amino groups, nitrile groups and isocyanate groups. The electrolyte enables the battery to have good cycle performance and storage performance.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application relates to the technical field of battery electrolytes, and in particular to an electrolyte and a battery. Background Art

[0002] Lithium-ion batteries have been widely used in mobile terminal devices, electric vehicles and other fields. Sodium-ion batteries have a similar energy storage mechanism to lithium-ion batteries, and sodium resources are more abundant on the earth, which makes sodium-ion batteries more likely to meet the low-cost demand for large-scale energy storage devices in the future.

[0003] Both lithium batteries and sodium batteries have certain performance deficiencies that affect their large-scale application. For example, there is inevitably a certain amount of water in the battery electrolyte. Water will cause the fluorine-containing electrolyte salts or other components in the electrolyte to hydrolyze and generate HF. The presence of HF will aggravate the dissolution of metal ions in the battery positive electrode material and reduce the stability of the interface film on the positive and negative electrode sides, thereby reducing the battery's cycle performance and storage performance (especially high-temperature storage performance).

[0004] Among them, adding film-forming additives to battery electrolytes has become one of the common means to improve battery cycle performance, but this usually cannot guarantee that the battery has both good cycle performance and high-temperature storage performance. Summary of the invention

[0005] In view of this, the present application provides an electrolyte containing specific additives to ensure that the lithium / sodium battery containing the electrolyte has both good cycle performance and storage performance.

[0006] Specifically, the first aspect of the present application provides an electrolyte, which includes an electrolyte salt, a solvent, and at least one additive A as shown in formula (I):

[0007]

[0008] In formula (I), at least one pair of R1 and R4, or R2 and R3, contains an amino group, and the other pair contains at least one of an amino group, a nitrile group, and an isocyanate group.

[0009] The above electrolyte contains additive A, which contains a pyridine ring in its structure and contains amino, nitrile and isocyanate substituents on the pyridine ring, which makes additive A have good alkalinity and can effectively reduce the HF content in the electrolyte, thereby effectively inhibiting the dissolution of transition metal ions on the positive electrode side of the battery, improving the stability of the interface film on the positive and negative electrode sides, and ensuring that the battery has good room temperature cycle performance and high temperature storage performance.

[0010] The second aspect of the present application provides a battery, wherein the electrolyte described in the first aspect of the present application is built in the battery, wherein the battery may be a sodium ion battery, or a lithium ion battery, etc.

[0011] The battery using the above electrolyte can better balance good room temperature cycle performance and high temperature storage performance, as well as lower room temperature impedance. DETAILED DESCRIPTION

[0012] The embodiments of the present application provide an electrolyte that enables a battery to have both good cycle performance and storage performance.

[0013] Specifically, the electrolyte provided in the embodiment of the present application includes an electrolyte salt, a solvent, and at least one additive A as shown in formula (I):

[0014]

[0015] In formula (I), at least one pair of R1 and R4, or R2 and R3, contains an amino group (-NH2), and the other pair contains at least one of an amino group (-NH2), a nitrile group (-CN), and an isocyanate group (-NCO).

[0016] The electrolyte mentioned above contains additive A, the structure of which contains a weakly alkaline pyridine ring, and the pyridine ring contains weakly alkaline substituents such as amino, nitrile, and isocyanate groups, which makes additive A have good alkalinity and can effectively reduce the HF content in the electrolyte, thereby effectively inhibiting the dissolution of transition metal elements on the positive electrode side, improving the structural stability of the positive electrode material, and improving the stability of the interface film on the positive and negative electrode sides, ensuring that the battery's cycle performance and high-temperature storage performance are both good. In addition, while reducing the HF content in the electrolyte, the additive A can also inhibit the formation of MF salts with low conductivity on the surface of the negative electrode of the battery due to the presence of HF (M represents active ions involved in energy storage / release in the battery, such as Li + Or Na + ), improve the battery’s rate performance.

[0017] The specific explanation of the above "at least one pair of R1 and R4, R2 and R3 contains an amino group, and the other pair contains at least one of an amino group, a nitrile group, and an isocyanate group" is as follows: R1 and / or R4 may contain an amino group, and R2 and / or R3 may independently contain at least one of an amino group, a nitrile group, and an isocyanate group (R2 and R3 may be the same or different groups); or R2 and / or R3 may contain an amino group, and R1 and / or R4 may independently contain at least one of an amino group, a nitrile group, and an isocyanate group (R1 and R4 may be the same or different groups). Among them, the amino group, the nitrile group, the isocyanate group, etc. may be directly connected to the pyridine ring in formula (I), or may be connected to the pyridine ring in formula (I) through a certain connecting group (such as an alkylene group, a cycloalkylene group, etc.).

[0018] In some embodiments of the present application, one pair of R1 and R4, R2 and R3 is an amino group, and the other pair is at least one of a nitrile group and an isocyanate group. In this case, R1, R4, R2, and R3 are all directly connected to the pyridine ring in formula (I). Specifically, R1 and R4 may be -NH2, R2 and R3 may be -CN, or both may be -NCO, or one may be -CN and the other may be -NCO; R2 and R3 may be -NH2, R1 and R4 may be -CN, or both may be -NCO, or one may be -CN and the other may be -NCO.

[0019] In this case, under the premise that the presence of pyridine ring and amino group can ensure the good alkalinity of additive A, the nitrile group and isocyanate group can also complex the metal ions in the positive electrode material of the battery to form a protective film on the surface of the positive electrode, inhibit the interfacial side reaction between the positive electrode material and the electrolyte, inhibit the decomposition of the electrolyte and the dissolution of the positive electrode metal ions; and can reduce the damage to the negative electrode SEI film caused by the deposition of metal ions dissolved from the positive electrode to the negative electrode side, thereby better improving the battery's cycle performance and high-temperature storage performance.

[0020] In the embodiment of the present application, the additive A includes at least one of the following compounds:

[0021]

[0022] Among them, the substances represented by the above formulas (i-1) to (i-6) have a more obvious effect on improving the cycle performance and high-temperature storage performance of the battery containing the above-mentioned electrolyte, and reducing the room-temperature impedance of the battery compared to the substance represented by formula (i-7). They also stabilize the positive electrode interface and reduce the dissolution of positive electrode transition metal elements, and are particularly effective in inhibiting the dissolution of vanadium elements in vanadium-containing sodium positive electrode materials.

[0023] In the embodiment of the present application, the total content of the additive A in the electrolyte is 0.01wt%-5wt%, for example, specifically 0.02wt%, 0.05wt%, 0.1wt%, 0.2wt%, 0.5wt%, 0.8wt%, 1.0wt%, 1.5wt%, 2.0wt%, 2.5wt%, 3.0wt%, 3.5wt%, 4.0wt%, 4.5wt%, etc. An appropriate amount of additive A can effectively improve the cycle performance and high temperature storage performance of the battery of the above-mentioned electrolyte without deteriorating the battery impedance and increasing adverse reactions such as gas production. In some embodiments, the total content of additive A in the electrolyte is 1wt%-3wt%.

[0024] In some embodiments of the present application, the electrolyte further contains a film-forming additive. The film-forming additive can inhibit the battery electrode material (i.e., positive electrode material, negative electrode material) from falling off from the current collector and help form a relatively stable electrolyte interface film. Among them, the above-mentioned negative electrode film-forming additive may include one or more of fluoroethylene carbonate (FEC), vinylene carbonate (VC), vinyl carbonate (VEC), vinyl sulfate (DTD), 1,3-propane sultone, and sodium difluorophosphate (NaPO2F2), but is not limited thereto.

[0025] The battery electrolyte contains both the additive A and the film-forming additive. With the synergistic cooperation of the additive A and the film-forming additive, the membrane components of the SEI membrane (solid electrolyte interface) on the negative electrode side of the battery and the CEI membrane (cathode electrolyte interface) on the positive electrode side are regulated, and the high-impedance components such as fluoride (such as LiF and NaF) of the active ions are reduced, so that the stability of the SEI membrane and the CEI membrane is further improved, thereby ensuring that the battery has excellent cycle performance.

[0026] In an embodiment of the present application, the total content of the film-forming additive in the electrolyte is 0.01wt%-7wt%, for example, specifically 0.02wt%, 0.05wt%, 0.1wt%, 0.2wt%, 0.5wt%, 0.8wt%, 1.0wt%, 1.5wt%, 2.0wt%, 2.5wt%, 3.0wt%, 3.5wt%, 4.0wt%, 4.5wt%, 5.0wt%, 5.5wt%, 6.0wt%, 6.5wt%, 6.9wt%, etc. In some embodiments, the total content of the film-forming additive in the electrolyte is 1wt%-7wt%.

[0027] In some embodiments of the present application, in the electrolyte, the mass ratio of the film-forming additive to the additive A is 1:(1-6). In this case, the synergistic effect between the film-forming additive and the additive A is better, and the improvement effect on the cycle performance, high temperature storage performance, and rate performance of the battery is more obvious. Specifically, the mass ratio can be 1.2, 1.5, 2, 3, 4, 5, 5, 5.5, 6, etc. In some embodiments, the mass ratio is 1:(1-5), further 1:(1.2-5), or 1:(1.2-3), etc.

[0028] In the embodiment of the present application, the electrolyte salt is a sodium salt or a lithium salt. When the electrolyte salt is a sodium salt, the electrolyte is suitable for sodium ion batteries. When the electrolyte salt is a lithium salt, the electrolyte is suitable for lithium ion batteries.

[0029] In some embodiments, the electrolyte salt is a sodium salt. Wherein, the sodium salt includes one or more of sodium hexafluorophosphate (NaPF6), sodium difluorophosphate (NaPF2O2), sodium nitrate (NaNO3), sodium perchlorate (NaClO4), sodium bis(oxalatoborate) (NaBC4O8), sodium difluorooxalatoborate (abbreviated as NaDFOB, chemical formula NaBC2F2O4), sodium bis(trifluoromethylsulfonyl imide) (molecular formula NaN(SO2CF3)2) and sodium bis(fluorosulfonyl imide) (NaN(SO2F)2), and at least includes sodium hexafluorophosphate. Wherein, sodium hexafluorophosphate, as an electrolyte sodium salt in sodium battery electrolyte, has good thermal stability, high ionic conductivity, and good film-forming effect. The concentration of sodium hexafluorophosphate in the electrolyte may be 0.6 mol / L-1.2 mol / L, for example, 0.7 mol / L, 0.8 mol / L, 0.9 mol / L, 1.0 mol / L, 1.1 mol / L, etc.

[0030] In some other embodiments of the present application, the electrolyte salt is a lithium salt. The lithium salt may include lithium hexafluorophosphate (LiPF6), lithium tetrafluoroborate (LiBF4), lithium hexafluoroarsenate (LiAsF6), lithium hexafluoroantimonate (LiSbF6), lithium perchlorate (LiClO4), lithium bis(oxalate borate) (LiBOB), lithium difluorooxalate borate (LiDFOB), lithium bis(trifluoromethylsulfonyl)imide (abbreviated as LiFSI, molecular formula LiN(SO2F)2), lithium bis(trifluoromethylsulfonyl)imide (abbreviated as LiTFSI, molecular formula LiN(SO2CF3)2), lithium bis(perfluoroethylsulfonyl)imide (LiN(C2F5SO2)2), lithium trifluoromethylsulfonate (LiCF3SO3), lithium perfluorobutylsulfonate (LiC4F9SO3) One or more. Among them, there is no special requirement for the lithium salt content in the electrolyte, and it can refer to the conventional amount in the art. In some embodiments of the present application, the lithium salt includes lithium hexafluorophosphate. Lithium hexafluorophosphate has good thermal stability, high ionic conductivity, and good film-forming effect. The concentration of lithium hexafluorophosphate in the electrolyte can be 0.6 mol / L-1.2 mol / L, for example, 0.7 mol / L, 0.8 mol / L, 0.9 mol / L, 1.0 mol / L, 1.1 mol / L, etc.

[0031] In the embodiment of the present application, the solvent includes a carbonate solvent. Wherein, the carbonate solvent may include a cyclic carbonate and / or a linear carbonate. Wherein, the cyclic carbonate may include at least one of propylene carbonate (PC), ethylene carbonate (EC), butylene carbonate, halogenated ethylene carbonate, etc. Linear carbonate may include at least one of dimethyl carbonate (DMC), ethyl methyl carbonate (EMC), diethyl carbonate (DEC), dipropyl carbonate (DPC), methyl propyl carbonate (MPC), ethyl propyl carbonate, etc. In some embodiments, the solvent includes a cyclic carbonate and a linear carbonate. The use of two types of carbonate solvents is conducive to ensuring that the ionic conductivity of the electrolyte is high, the viscosity is low, and the solubility of the electrolyte in it is good. Wherein, the volume ratio of cyclic carbonate and linear carbonate can be (2-8): (4-6). In some embodiments, the solvent includes PC, EMC and DMC.

[0032] The present application also provides a battery, in which the electrolyte of the present application is built in. The battery containing the electrolyte has good room temperature cycle performance and good high temperature storage performance, and also has good rate performance.

[0033] Specifically, the battery includes a battery housing, a battery cell contained in the battery housing, and the above-mentioned electrolyte of the embodiment of the present application, wherein the battery cell includes a positive electrode sheet, a negative electrode sheet, and a separator located between the positive electrode sheet and the negative electrode sheet.

[0034] The preparation method of the battery includes: stacking the positive electrode plate, the separator and the negative electrode plate in sequence to make a battery cell, accommodating the battery cell in a battery shell, injecting the above-mentioned electrolyte, and then sealing the battery shell to obtain a battery.

[0035] Among them, the negative electrode sheet, the positive electrode sheet, and the separator are all conventional choices in the battery field. The separator may include but is not limited to a single-layer PP (polypropylene) film, a single-layer PE (polyethylene) film, a double-layer film PP / PE, a double-layer film PP / PP, and a three-layer PP / PE / PP polymer separator, or a non-woven fabric, etc. Generally, the positive electrode sheet includes a positive electrode current collector and a positive electrode material layer disposed on the positive electrode current collector; the positive electrode material layer includes a positive electrode active material, a binder, and an optional conductive agent. Similarly, the negative electrode sheet includes a negative electrode current collector and a negative electrode material layer disposed on the negative electrode current collector, and the negative electrode material layer may include a negative electrode active material, a binder, and an optional conductive agent.

[0036] Among them, for sodium ion batteries, the negative electrode active material may include but is not limited to soft carbon, hard carbon, sodium titanate and one or more metals that can form alloys with sodium. The positive electrode active material may include but is not limited to sodium vanadium phosphate (Na3V2(PO4)3), NaFePO4, NaCoPO4, sodium transition metal oxides (such as Na x CoO2、Na x MnO2、NaNi 0.33 Fe 0.33 Mn 0.33 O2, etc.) or more.

[0037] The above batteries can be used in electrical equipment such as 3C products (such as mobile phones, laptops, tablets, pen-input computers, e-book players, wearable devices, etc.), electric vehicles (such as electric cars, electric motorcycles, electric bicycles, etc.); they can also be used in energy storage systems.

[0038] The technical solution of the embodiment of the present application is further explained below with multiple embodiments.

[0039] Example 1

[0040] A preparation method for an electrolyte for a sodium ion battery includes: mixing propylene carbonate (PC), ethyl methyl carbonate (EMC), and diethyl carbonate (DMC) in a volume ratio of 25:65:10 to obtain a mixed solvent; then adding a certain amount of sodium hexafluorophosphate (NaPF6) as an electrolyte sodium salt to the mixed solvent, and after the sodium salt is completely dissolved, adding film-forming additives vinyl sulfate (DTD) and film-forming additives fluoroethylene carbonate (FEC) and additive A as shown in the above formula (i-1), stirring until all solid substances are completely dissolved to obtain the desired electrolyte. The concentration of NaPF6 in the electrolyte is 0.8 mol / L, the concentration of DTD is 1 wt%, the concentration of FEC is 5 wt%, and the concentration of additive A shown in formula (i-1) is 1 wt%.

[0041] A method for preparing a sodium ion battery, comprising:

[0042] (1) Preparation of positive electrode sheet: The positive electrode active material Na3V2(PO4)3, the conductive agent Super p, the conductive agent carbon nanotubes, and the binder PVDF (polyvinylidene fluoride) are mixed in a solvent at a mass ratio of 95:2.3:0.7:2 to prepare a positive electrode slurry; the positive electrode slurry is coated on both sides of the positive electrode current collector aluminum foil, and the surface density of the single-side coating is 30g / m 2 , dried at 85°C and then cold pressed; then trimmed, cut into pieces, and slit, and then dried at 85°C under vacuum conditions for 4 hours, and the tabs were welded to obtain the positive electrode sheet.

[0043] (2) Preparation of negative electrode sheet: The negative electrode active material (hard carbon) is mixed with the conductive agent Super p, the binder CMC, and the binder SBR (styrene-butadiene rubber latex) in a mass ratio of 95:1.5:1:2.5 to prepare a negative electrode slurry; the negative electrode slurry is coated on both sides of the positive electrode current collector copper foil, and the negative electrode sheet is obtained after drying and rolling.

[0044] (3) Assembly of sodium ion battery: In a glove box, the positive electrode sheet, separator and negative electrode sheet are stacked in order and wound into a square battery cell (thickness 4.7 mm, width 55 mm, length 60 mm), which is then placed in a battery case and welded, and then the battery cell placed in the case is vacuum baked at 75°C for 10 hours to reduce the water content. Thereafter, the electrolyte is injected into the battery case, and the battery case is sealed to manufacture a sodium ion battery. After the battery was left to stand for 24 hours, it was formed and activated. Specifically, it was first charged to 4.2V at a constant current of 0.1C (180mA), and then charged at a constant voltage of 4.2V until the current dropped to 0.05C (90mA); then discharged to 3.0V at 0.2C (180mA), and the above charging and discharging were repeated twice; finally, the battery was charged to 3.8V at 0.2C (180mA) to obtain a battery that can be used for electrochemical performance testing.

[0045] Example 2

[0046] The electrolyte of Example 2 is different from that of Example 1 only in that the concentration of the additive A represented by formula (i-1) in the electrolyte is 2 wt %.

[0047] According to the method described in Example 1, the electrolyte of Example 2 was prepared into a sodium ion battery.

[0048] Example 3

[0049] The electrolyte of Example 3 is different from that of Example 1 only in that the concentration of the additive A represented by formula (i-1) in the electrolyte is 3 wt %.

[0050] According to the method described in Example 1, the electrolyte of Example 3 was prepared into a sodium ion battery.

[0051] Example 4

[0052] The electrolyte of Example 4 is different from that of Example 1 only in that additive A is a substance represented by formula (i-7), and its concentration in the electrolyte is still 1 wt %.

[0053] According to the method described in Example 1, the electrolyte of Example 4 was prepared into a sodium ion battery.

[0054] Example 5

[0055] The electrolyte of Example 5 is different from that of Example 1 only in that additive A is a substance represented by formula (i-3), and its concentration in the electrolyte is still 1 wt %.

[0056] According to the method described in Example 1, the electrolyte of Example 5 was prepared into a sodium ion battery.

[0057] Example 6

[0058] The electrolyte of Example 6 is different from that of Example 1 only in that additive A is a substance represented by formula (i-2), and its concentration in the electrolyte is still 1 wt %.

[0059] According to the method described in Example 1, the electrolyte of Example 6 was prepared into a sodium ion battery.

[0060] Example 7

[0061] The electrolyte of Example 7 is different from that of Example 1 only in that additive A is a substance represented by formula (i-4), and its concentration in the electrolyte is still 1 wt %.

[0062] According to the method described in Example 1, the electrolyte of Example 7 was prepared into a sodium ion battery.

[0063] Example 8

[0064] The electrolyte of Example 8 is different from that of Example 1 only in that the concentration of the additive A represented by formula (i-1) in the electrolyte is 5 wt %.

[0065] According to the method described in Example 1, the electrolyte of Example 8 was prepared into a sodium ion battery.

[0066] Example 9

[0067] The electrolyte of Example 9 is different from that of Example 1 only in that the concentration of the additive A represented by formula (i-1) in the electrolyte is 0.01 wt %.

[0068] According to the method described in Example 1, the electrolyte of Example 9 was prepared into a sodium ion battery.

[0069] Example 10

[0070] The electrolyte of Example 10 is different from that of Example 3 only in that the electrolyte does not contain a film-forming additive, that is, the contents of DTD and FEC in the electrolyte are both zero.

[0071] According to the method described in Example 1, the electrolyte of Example 10 was prepared into a sodium ion battery.

[0072] Embodiment 11

[0073] The electrolyte of Example 11 is different from that of Example 3 only in that the content of the film-forming additive in the electrolyte is changed, wherein the content of DTD is 0.005% and the content of FEC is 0.005%.

[0074] According to the method described in Example 1, the electrolyte of Example 11 was prepared into a sodium ion battery.

[0075] Example 12

[0076] The electrolyte of Example 12 is different from that of Example 3 only in that the content of the film-forming additive in the electrolyte is changed, wherein the content of DTD is 0.5 wt % and the content of FEC is 0.5 wt %.

[0077] According to the method described in Example 1, the electrolyte of Example 12 was prepared into a sodium ion battery.

[0078] Example 13

[0079] The electrolyte of Example 13 is different from that of Example 3 only in that the composition of the film-forming additives in the electrolyte is changed, specifically containing VC at a concentration of 2 wt % and FEC at a concentration of 5 wt %.

[0080] According to the method described in Example 1, the electrolyte of Example 13 was prepared into a sodium ion battery.

[0081] Embodiment 14

[0082] The difference between the electrolyte of Example 14 and Example 3 is that the sodium salt in the electrolyte contains, in addition to NaPF6, sodium difluorooxalatoborate (abbreviated as NaDFOB), and its concentration in the electrolyte is 0.2 mol / L.

[0083] According to the method described in Example 1, the electrolyte of Example 14 was prepared into a sodium ion battery.

[0084] In order to highlight the beneficial effects of the embodiments of the present application, the following comparative examples 1-4 are provided.

[0085] Comparative Example 1

[0086] The difference between Comparative Example 1 and Example 1 is that the electrolyte does not contain the additive A represented by formula (i-1), that is, its content is 0.

[0087] According to the method described in Example 1, the electrolyte of Comparative Example 1 was prepared into a sodium ion battery.

[0088] Comparative Example 2

[0089] The electrolyte of Comparative Example 2 is different from that of Example 1 only in that the additive A represented by formula (i-1) in Example 1 is replaced by a 2,6-diaminopyridine additive, and the concentration of the 2,6-diaminopyridine additive in the electrolyte is 1 wt %.

[0090] According to the method described in Example 1, the electrolyte of Comparative Example 2 was prepared into a sodium ion battery.

[0091] Comparative Example 3

[0092] The electrolyte of Comparative Example 3 is different from that of Example 1 only in that the additive A represented by formula (i-1) in Example 1 is replaced by a 2,6-dinitrile pyridine additive, and the concentration of the additive in the electrolyte is 1 wt %.

[0093] According to the method described in Example 1, the electrolyte of Comparative Example 3 was prepared into a sodium ion battery.

[0094] Comparative Example 4

[0095] The electrolyte of Comparative Example 4 is different from that of Example 1 only in that the electrolyte does not contain the additive A represented by formula (i-1), nor does it contain the film-forming additives DTD and FEC.

[0096] The sodium ion batteries of the above embodiments and comparative examples were subjected to the following performance tests:

[0097] a) Battery normal temperature calibration capacity test: At room temperature (25°C), each sodium battery is charged at 0.33C constant current and constant voltage to an upper limit voltage of 4.5V, and then charged at 4.5V constant voltage to a cut-off current of 0.05C; after 30 minutes of storage; then discharged at 0.33C constant current to a lower limit voltage of 3.0V, and after 30 minutes of storage; the above charge and discharge steps are repeated 3 times, and the capacity discharged for the third time is recorded as C0, in Ah.

[0098] b) Battery DC internal resistance (DCIR) test at 25°C: At 25°C, each sodium battery is first charged at a constant current of 1C to a voltage of 4.5V, and then charged at a constant voltage to a cut-off current of 0.05C; then discharged at 1C0 to a battery capacity of 0.5C0 (i.e., the battery state of charge (SOC) is adjusted to 50% SOC), left to stand for 10 minutes, and the battery voltage after standing for 10 minutes is recorded as V1; then the battery is discharged at 1.5C0 for 30 seconds, and the battery voltage after the discharge is recorded as V2, and the DCIR of the battery is calculated. Wherein, DCIR = (V1-V2) / 1.5C0.

[0099] c) Room temperature cycle performance test: At room temperature (25°C), each battery is first charged at a constant current of 0.5C to a voltage of 4.5V, and then charged at a constant voltage of 4.5V to a cut-off current of 0.05C; then the battery is discharged at a constant current of 1C to a cut-off potential of 3V, and the first discharge capacity C1 is recorded. The above charging and discharging steps are repeated for a certain number of cycles until the capacity retention rate of the battery (i.e., the ratio of the discharge capacity after a certain number of cycles to C1) is below 80%, and the number of cycles n is recorded as the life of the battery.

[0100] d) Vanadium (V) element dissolution test: Each battery that has reached the cycle life in the above step (c) is disassembled, the negative electrode plate is taken out, and after being soaked in solvent, it is dried and the powder is scraped off. The collected powdered negative electrode material is tested using an inductively coupled plasma spectrometer (ICP) to measure the vanadium (V) content in the powder material to obtain the vanadium (V) content dissolved from the positive electrode to the negative electrode side.

[0101] e) Capacity retention test after 14-day storage at 60°C: After each battery is charged and discharged twice at a rate of 0.33C at 25°C, each battery is charged to a fully charged state at 0.33C, and then each fully charged battery is stored in a high temperature environment of 60°C for 14 days, and then discharged at 0.33C at 25°C. The obtained discharge capacity is divided by the above discharge capacity C0 to obtain the discharge capacity retention rate after high-temperature storage, which is used to evaluate the high-temperature storage performance of the battery.

[0102] f) Rate performance test: At 25°C, each battery was charged to 4.5V at 0.33C constant current and constant voltage, and then discharged to the lower limit voltage of 3V at 4C to obtain the discharge capacity C 4c , where C 4c The ratio to the aforementioned C0 is the battery’s 4C capacity retention rate.

[0103] The above performance test results of each battery are summarized in Table 1 below.

[0104] Table 1

[0105]

[0106] From the comparison of Examples 1, 4, 5, 6, 7 and Comparative Examples 1-3 in Table 1, it can be seen that when the electrolyte contains the same amount of conventional film-forming additives, the other additives in the electrolyte are the additive A provided by the present application, which is better than the additives 2,6-dinitrile pyridine and 2,6-dinitrile pyridine used in Comparative Examples 2-3 in improving the room temperature cycle performance, high temperature storage performance, and room temperature impedance of the sodium battery, and they are all better than Comparative Example 1 without other additives. In addition, Examples 1, 4-7 and Comparative Examples 1-3 are also higher than Comparative Example 4 without conventional film-forming additives and Additive A in the electrolyte.

[0107] In addition, from the comparison between Examples 1, 4, 5, 6, and 7, it can be seen that when the content of additive A is the same but the structural formula is different, the additive A shown in formula (i-7) containing only an amino group in its structure has a slightly lower improvement effect on the overall performance of the battery than the additive A containing a nitrile group, one of an isocyanate group and an amino group in its structure (as shown in formulas (i-1) to (i-4)).

[0108] From the comparison between Example 10 and Example 3, it can be seen that the additive in the electrolyte is only the additive A in the present application. Compared with the electrolyte containing both the additive A provided in the examples of the present application and the conventional film-forming additive, the improvement effect on the room temperature cycle performance and high temperature storage performance of the sodium ion battery is reduced to a certain extent, which indicates that the two additives have a certain synergistic effect; however, the effect of Example 10 is still significantly better than that of Comparative Examples 1-3.

[0109] From the comparison between Example 3 and Examples 11, 12, and 13, it can be seen that when the electrolyte contains the additive A of the present application, when the total addition amount of conventional film-forming additives in the electrolyte is in the range of 0.01%-7%, the room temperature cycle performance of the battery (including room temperature cycle life, vanadium element dissolution amount, etc.) can be improved.

[0110] From the comparison between Examples 1-3 and 8-9, it can be seen that by adjusting the amount of additive A shown in formula (i-1) in the electrolyte, the room temperature cycle stability, room temperature impedance, rate performance and high temperature storage performance of the battery can be adjusted. Moreover, when the mass ratio of the conventional film-forming additive to the additive A is in the range of 1: (1-6), the synergistic effect between the additive A provided in the present application and the conventional film-forming additive is better, and the improvement effect on the cycle performance, high temperature storage performance and rate performance of the battery is more obvious.

[0111] The above is an exemplary embodiment of the present application, and its description is relatively specific and detailed, but it cannot be understood as limiting the scope of the present invention. It should be pointed out that for ordinary technicians in this field, several modifications and improvements can be made without departing from the concept of the present invention, which all belong to the protection scope of the present invention.

Claims

1. An electrolyte, characterized in that: The electrolyte comprises an electrolyte salt, a solvent, and at least one additive A as shown in formula (I): In formula (I), at least one pair of R1 and R4, or R2 and R3, contains an amino group, and the other pair contains at least one of an amino group, a nitrile group, and an isocyanate group.

2. The electrolyte according to claim 1, characterized in that One pair of R1 and R4, and one pair of R2 and R3 is an amino group, and the other pair is at least one of a nitrile group and an isocyanate group.

3. The electrolyte according to claim 2, characterized in that The additive A comprises at least one of the following compounds:

4. The electrolyte according to claim 1, characterized in that The total content of the additive A in the electrolyte is 0.01 wt%-5 wt%.

5. The electrolyte according to any one of claims 1 to 4, characterized in that The electrolyte further comprises a film-forming additive; wherein the film-forming additive comprises one or more of fluoroethylene carbonate, vinylene carbonate, vinyl carbonate, vinyl sulfate, 1,3-propane sultone, and sodium difluorophosphate.

6. The electrolyte according to claim 5, characterized in that The total content of the film-forming additive in the electrolyte is 0.01 wt % to 7 wt %.

7. The electrolyte according to claim 5, characterized in that In the electrolyte, the mass ratio of the film-forming additive to the additive A is 1:(1-6).

8. The electrolyte according to any one of claims 1 to 7, characterized in that The electrolyte salt is a sodium salt or a lithium salt.

9. The electrolyte according to claim 8, characterized in that The sodium salt includes one or more of sodium hexafluorophosphate, sodium difluorophosphate, sodium nitrate, sodium perchlorate, sodium bisoxalatoborate, sodium difluorooxalatoborate, sodium bistrifluoromethylsulfonyl imide and sodium bisfluorosulfonyl imide, and at least includes sodium hexafluorophosphate.

10. The electrolyte according to claim 8, characterized in that The sodium salt includes sodium hexafluorophosphate; the concentration of the sodium hexafluorophosphate in the electrolyte is 0.6 mol / L-1.2 mol / L.

11. The electrolyte according to any one of claims 1 to 10, characterized in that: The solvent includes a carbonate solvent.

12. A battery, characterized in that: The battery contains the electrolyte according to any one of claims 1 to 11.

Citation Information

Patent Citations

  • Electrolyte for 4.5 V lithium ion battery

    CN103441303A

  • Electrolyte for fluorine-containing solvent and pyridine additive and lithium ion battery using same

    CN109687022A

  • Electrolytic solution and electrochemical device thereof

    CN112310478A

  • Lithium ion battery electrolyte and preparation method thereof, lithium ion battery and electric equipment

    CN115763979A

  • Nonaqueous electrolyte and nonaqueous electrolyte secondary battery

    JP2002093462A